The Politics of Disaster Risk Governance and Neo-Extractivism in Latin America - Pereira Covarrubias, Andrés (2020)
Latin America is one of the regions facing many disasters with some of the worse impacts. The current governance model has not proven successful in disaster risk reduction. This article aims to theoretically analyse the relationship between ideal regional disaster risk governance (DRG) and the actual production of disaster risk in Latin America. From the so-called ‘vulnerability paradigm’ and a regional standpoint, this analysis contributes to the debate with a specific focus on ‘neo-extractivism.’ Pointing mainly to sociopolitical processes triggered as of the early 2000s in Latin America, ‘neo-extractivism’ relates to a regional ecological-political pattern of intensive natural resource exploitation. The first part of this article presents a regional overview of DRG and its scope in disaster risk reduction, analysing its ineffectiveness through the lens of the neoliberal governmentality problem. The second part deals with the issue of ‘neo-extractivism’ to outline the actual links between the political arena, the development discourse, and the creation of vulnerability and new hazards in the region’s contemporary social processes. We show a correlation between political arrangements and environmental degradation that brings about both disasters and an increase in disaster risk. ‘Neo-extractivism’ foregrounds the political conditions for the implementation of regional DRG and reveals how its projections within the development discourse relate incongruously with the essential factors of disaster risk.